Evaluation of the Effect of Demineralized Bone Matrix as a Scaffold on Pulp Revascularization of Immature Cat Teeth - Mehdi Dastorani; Jalil Modaresi; Ali Akhavan; Maziyar Manshaii; Fatemeh Ayatollahi
Introduction: The treatment of pulpal necrosis in an immature tooth with an open apex presents a unique challenge to the dentist. Revascularization is a new treatment procedure for the management of these cases. This study examined the ability of demineralized bone matrix as a scaffold to aid pulp revascularizaion of immature cat teeth.Materials & Methods: Sixteen immature teeth from 4 cats after preparation of access cavity and cleaning of canals, were placed into two groups; control group containing blood in canal and experimental group containing blood + demineralized bone matrix. Teeth were treated with revascularization technique and cats were followed up for four months. Then periapical radiographs were taken and analyzed for presence of apical radiolucencies, apical closure and thickening of root canal walls. The data were statistically analyzed using Fisher's exact test. 0.05 was established as a level of significance.Results: The two groups showed no statistical difference regarding presence of apical radiolucencies, apical closure and thickening of root canal walls. In control group, none of the teeth showed any apical radiolucencies and 75% of teeth showed apical closure and thickening of root canal walls. In experiments group, none of the teeth showed any apical radiolucencies, 90.9% of teeth showed apical closure and 81.8% showed thickening of root canal walls.Conclusion: Based on the results of this study, the demineralized bone matrixes do not have adverse effect on revascularization procedure and can be used as a scaffold in this technique.